Unlocking FinTech’s Potential: The Crucial Role of Cybersecurity and Trust in Malaysia - Rozali, Salfariza; Muhamat, Amirul Afif Muhamat; Humaidi, Norshima; Abd Rashid, Mohd Hafiz (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The rapid emergence of financial technology (FinTech) has revolutionized the banking industry, propelling it into the digital age. However, this transformative shift has also brought critical concerns regarding data protection and cybersecurity to the forefront, issues that remain unresolved and pose significant challenges for the sector. Cybersecurity and trust are paramount as they directly influence customer adoption and the overall success of FinTech initiatives. This study delves into existing research within the Malaysian context, analyzing previous findings to identify the potential precursors that have shaped current trends in the region. By examining historical data, socio-economic factors, and relevant policies, this research aims to uncover the underlying forces that have contributed to the present-day landscape.